Editorial - Pathrapankal , Joseph (Journal of Dharma, 1987)
Time and again such challenges shake the very foundation of religion, and no religion is an exception to this. Whenever religions become a mere matter of ideology, wherever religions deviate from their radical demands, there appear people who raise questions and propose new ways of affirming their religious commitment. Mother Teresa of Calcutta and her mission are a typical case of such a religious commitment. Through her challenging life and the message she has communicated for humanity, she is universally recognized as a great person with a great mission in our times. A characteristic phenomenon of our times is that many of the challenges religions face are very much of the same nature. Consequently the kind of religious commitment that is expected of all religions is very much the same. Practically all religions are now committed to a rejection of a narrow- minded approach in favour of a broad-minded one in their inter-religious relationships. They now speak a language of complementarity over against intolerance and hatred. Likewise all religions are concerned about their this-wordly dimensions over against aone-sided understanding of religion as an other-wordly reality. As a result, religions are asked to get involved in the secular dimensions of human life as the sure way of meeting God and finding the real meaning of religion.